Introduktion av fjärropererade passagerarfärjor i nationell sjöfart: Kvalitativ studie av risker och juridiska utmaningar - Grönberg, Lina (My University, 2025)
Remotely operated passenger ferries have the potential to change maritime transport, but current regulations are designed for traditional ships with onboard crews. This study examines how Swedish national regulations can be applies to remotely operated passenger ferries in commercial operations within Swedish territorial waters. It identifies legal challenges, implementation risks, and maps ongoing projects, tests and future visions. The study was conducted at Chalmers university of technology using av qualitative research approach. A legal analysis of The Swedish Maritime Code (1994:1009), The Vessel Safety Act (2003:364) and The Vessell Safety Ordinance (2003:438) identified 64 regulatory obstacles, with crew requirements and the shipmasters’ role being major issues. The literature review highlights the lack of a clear definition of autonomous ships, which creates uncertainty in legal interpretation. The study identifies several risks associated with the implementation of remotely operated passenger ferries, including communication failures, cyberattacks and technical malfunctions that may affect safety. Operational challenges include emergency evacuation risks, such as in the event of a fire, as well as unclear responsibility in case of incidents. The SWOT-analysis highlights opportunities, threats, strengths and weaknesses in implementing remotely operated passenger ferries and integrates the result from the different methods into a comprehensive overview. The study highlights the advantages of Sweden rapidly adapting its national regulations, which could position the country as a leading actor with the ability to influence developments and drive innovation. At the same time, a swift implementation and regulatory adjustment entail risks. If Sweden establishes its own rules before international guidelines are set, this could lead to future needs for extensive revisions, high economic costs and legal uncertainties. There is also a lack of legal precedents, creating uncertainties regarding legal issues such as owner liability.
Keywords: Autonom; sjöfart; fjärropererade fartyg; passagerarfärjor; obemannade fartyg; MASS; Autonomous; remotely operated vessels; passenger ferries; unmanned vessels